ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI - Yuliantari, Ni Luh; Baskara, I Gde Kajeng (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023, 2023)
The purpose of this study was to determine the increase or decrease in the company's financial performance after mergers and acquisitions. This research was conducted on non-financial companies listed on the Indonesia Stock Exchange that carried out mergers and acquisitions for the period 2010-2018. The number of companies used as a sample is 32 companies using the census method, namely the entire population is used as a sample. The analytical technique used is the Paired-Sample T-test. Based on the results of the analysis, it was found that the financial performance as measured by the Current Ratio, Total Assets Turnover, and Earning Per Share decreased but was not significant, and for Return On Assets it showed a significant decrease while the Debt to Equity Ratio experienced an insignificant increase which means the position Financial risk is more risky after companies carry out mergers and acquisitions. The motive for companies to do mergers and acquisitions is managerial advantage where managers may have other motives besides maximizing the value of the company. Companies that will carry out mergers and acquisitions in order to achieve success must make preparations by looking at the financial condition and management of the company to be acquired or the company that will conduct the merger